2022
DOI: 10.1136/bmjopen-2021-057285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of anaemia in childhood bacterial meningitis: a secondary analysis of prospectively collected data from clinical trials in Finland, Latin America and Angola

Abstract: ObjectivesTo describe the prevalence and severity of anaemia and to examine its associations with outcome in children with bacterial meningitis (BM).DesignSecondary analysis of descriptive data from five randomised BM treatment trials.SettingHospitals in Finland, Latin America and Angola.ParticipantsConsecutive children from 2 months to 15 years of age admitted with BM and who had haemoglobin (Hb) measured on admission.Outcome measuresPrevalence and degree of anaemia using the WHO criteria, and their associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Hemoglobin levels are decreased in FC [ 20 ], and anemia, mostly moderate, is a common presentation in children with bacterial meningitis, and it is also associated with poor outcomes [ 53 ]. Shi et al found that children in ICU with lower hemoglobin levels have higher mortality in severe community-acquired pneumonia [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin levels are decreased in FC [ 20 ], and anemia, mostly moderate, is a common presentation in children with bacterial meningitis, and it is also associated with poor outcomes [ 53 ]. Shi et al found that children in ICU with lower hemoglobin levels have higher mortality in severe community-acquired pneumonia [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Moderate to severe anemia is a known complication in severe disease and triples the odds for death in childhood bacterial meningitis (BM). 1,2 The principal causes of anemia in sub-Saharan Africa, in order of importance, but often combined, include malaria, other parasitic infections, sickle cell disease, undernutrition, and inadequate iron intake. 3 Opposite to the other risks for adverse outcomes from BM, severe anemia is mitigable or reversable by blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, anemia is highly prevalent in children. 1 , 2 Moderate to severe anemia is a known complication in severe disease and triples the odds for death in childhood bacterial meningitis (BM). 1 , 2 The principal causes of anemia in sub-Saharan Africa, in order of importance, but often combined, include malaria, other parasitic infections, sickle cell disease, undernutrition, and inadequate iron intake.…”
Section: Introductionmentioning
confidence: 99%